2018
DOI: 10.1111/jpc.14248
|View full text |Cite
|
Sign up to set email alerts
|

Enrolment in paediatric oncology early‐phase clinical trials: The health‐care professionals' perspective

Abstract: Aim Approximately 20–30% of children/adolescents with cancer will not respond to standard therapies. These children are usually offered experimental treatment in the form of an early‐phase clinical trial. We examined the perspectives of health‐care professionals (HCPs) regarding obtaining informed consent for early‐phase trials in paediatric oncology. Methods We collected survey data from 87 HCPs working in paediatric cancer centres across Australia and New Zealand. Results HCPs were, on average, 44 years old … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…For example, Hendersen et al demonstrated in their study of early phase gene therapy that while some participants may understand they are in a research study to generate generalizable knowledge, they may still have unrealistic expectations about the direct benefit of the therapy under study [38]. A recent survey of health care professionals working in pediatric cancer centres also demonstrated similar results to ours in that the majority of health care professionals surveyed believed perception of medical benefit for the child was a primary motivating factor for parents' consent for participation in earlyphase clinical trials [40]. Therapeutic misconception is a complex concept that warrants further investigation in the field of rare diseases.…”
Section: Discussionsupporting
confidence: 76%
“…For example, Hendersen et al demonstrated in their study of early phase gene therapy that while some participants may understand they are in a research study to generate generalizable knowledge, they may still have unrealistic expectations about the direct benefit of the therapy under study [38]. A recent survey of health care professionals working in pediatric cancer centres also demonstrated similar results to ours in that the majority of health care professionals surveyed believed perception of medical benefit for the child was a primary motivating factor for parents' consent for participation in earlyphase clinical trials [40]. Therapeutic misconception is a complex concept that warrants further investigation in the field of rare diseases.…”
Section: Discussionsupporting
confidence: 76%
“…Clinicians face the additional challenging task of managing informed consent consultations and addressing family expectations in a setting that often sits at the junction between research and clinical practice [15,16]. Not surprisingly, there is evidence that patients and their parents may misunderstand the aims of early phase oncology research [17] including the implications of genomic tumour profiling [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…For families, the following characteristics and behaviors were identified as potential barriers or facilitators of communication: parental preferences for disclosure, 57,61,67,74,82–87 family's expectations regarding disease course, 10,54,61,88–91 family's emotional state, 40,42,92–96 preparedness to receive difficult news, 39,41,61 comfort with the topic, 52,69,97–99 demonstrated priority/importance of the topic, 36,51,52,66 level of medical knowledge or education, 35,41,43,57,61,63,91,92,100,101 internal family functioning, 54,102,103 age of the child, 51,63,72,104–106 parental fears of harm to the child from communication, 41,92 and lack of fluency in the majority language 99,107–110 …”
Section: Resultsmentioning
confidence: 99%